A recurrence CFD study of heat transfer in a fluidized bed. (23rd November 2017) - Lichtenegger, T.; Peters, E.A.J.F.; Kuipers, J.A.M.; Pirker, S.
Highlights: Recurrent patterns in fluidized beds decouple fast dynamics from heat transfer. Based on short CFD-DEM simulations, we predict the evolution of such systems. Particle mean temperatures agree very well with recent experiments. Simulations are sped up by more than two orders of magnitude. Abstract: Significant progress in modeling and simulation techniques has opened the door to accurate descriptions of highly dynamic gas-solid flows. However, such investigations are limited to short durations by enormous computational costs, making long-term numerical experiments on slow processes like heat transfer unfeasible. We employ the potentially groundbreaking new approach recurrence CFD to decouple fast, recurrent dynamics from slower degrees of freedom. This allows us to study heat transfer in lab-scale fluidized beds consisting of about 57 000 and 95 000 particles ( T p, 0 = 90 ° C, T gas, in = 20 ° C ), respectively, at 1/300 of the runtime of conventional CFD-DEM simulations on the same hardware with hardly distinguishable evolutions of particle mean temperatures even after 60 s process time. A detailed performance analysis reveals possible future improvements on the way to industrial-size systems.